Re: Broadcasting Notice of Consultation CRTC 2017-183, Renewal of Société de télédiffusion du Québec licence, 2017-0830-7 - English Language Arts Network (ELAN); Rodgers, Guy (2018)
Keywords: Official Language Minority Community (OLMC)

Bell Media Must Restore Local Sports at CTV Montreal : QCGN - Quebec Community Groups Network (QCGN) (2017)

English-speaking Quebecers Like to See Themselves Reflected on CBC - Quebec Community Groups Network (QCGN) (2014)

CRTC Must Oblige Vidéotron to Restore English-language Community Television Station : Attention News Directors, Television, and Arts Reports - Quebec Community Groups Network (QCGN) (2013)

CRTC Decision on CBC License Renewal Good News for English-speaking Quebecers - Quebec Community Groups Network (QCGN) (2013)
Keywords: Official Language Minority Community (OLMC)

Comments on the Canada Media Fund's English Regional Production Policies by the English-language Arts Network of Quebec - English Language Arts Network (ELAN) (2009)
The Canadian Television Fund (CTF) has made the English-language regions synonymous with the official-language minority in Quebec. While regional policies overlap with official-language policies in many ways, they are each distinct and need to be addressed differently. The Official Languages Act gives the English-language minority in Quebec the same status as the French-language minority outside Quebec. However, the CTF has not recognized that the official-language minority community (OLMC) in Quebec has the same rights and legal status as the French-language minority outside Quebec. Thus, Montreal production is not given regional status for the BPE, nor is there a Quebec OLMC production fund similar to the production fund (FLPOQ) available to the French-language minority outside Quebec.
Keywords: Official Language Minority Community (OLMC)

Local Television Support for the Official-language Minority in Quebec - Magnetic North Associates (2009)
The Anglophone minority doesn’t lack access to English-language channels via satellite and cable distribution, but it is underserved in “regional reflection” and “local expression”. That is especially the case for the 200,000 Anglophones outside the greater Montreal area who have virtually no “regional reflection”. The reason for this inadequate regional programming can be traced to the lack of regional services available to the official language minority community (OLMC) in Quebec. There is no English-language educational channel, similar to TFO in Ontario, nor is there an English regional channel, or community channel.

[Plea to Save the CBC] - Quebec Community Groups Network (QCGN) (2009)

Re: Support of the Canadian Broadcasting Corporation (CBC) - Rodgers, Guy (2009)
Keywords: Official Language Minority Community (OLMC)

ELAN Speech to Parliamentary Committee on CBC Review - English Language Arts Network (ELAN) (2007)

Through the Looking Glass : A Comparison of Broadcast License Fees in Canada, Australia, the United Kingdom and the United States - Cox, Kirwan (2004)
The decision of a domestic broadcaster to commission a program from a producer, and the license fee paid by the broadcaster to that producer, is the foundation of the independent television production system in Canada. Most public funding for Canadian programming follows on the basis of these transactions. Unfortunately, that public funding is oversubscribed, and the production industry is chronically underfunded. Some suggest that part of this problem is the size of the Canadian broadcast license fee. Based on anecdotal evidence, it is argued that Canadian license fees are low by international standards. The purpose of this study is to see if Canadian license fees for English independent television programs are indeed low based on selected international and historical comparisons. If they are, why?